High-entropy porous ferric sodium pyrophosphate positive electrode material and preparation method thereof
Through high-entropy porous construction and coordinated interface carbon coating processing, a high-entropy porous sodium ferric pyrophosphate positive electrode material was prepared, which solved the problems of slow electronic transmission speed and long ion diffusion distance of existing sodium ion battery positive electrode materials, and realized the High-rate performance and stable electrochemical performance, suitable for the industrial production of sodium ion batteries.
Patent Information
- Application Number
- CN202411455509.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-14
AI Technical Summary
The existing sodium ion battery positive electrode materials have slow electron transfer speed, long ion diffusion distance, and scarce electroactive reaction sites, resulting in poor rate performance and cyclic stability, making it difficult to meet the requirements of energy storage applications.
High-entropy porous construction and interfacial carbon coating collaborative treatment were used to prepare a high-entropy porous sodium ferric pyrophosphate positive electrode material, which improved the structural stability and specific surface area of the material, and enhanced the electron transfer speed and ion diffusion ability.
It significantly improves the electron transfer speed, ion diffusion distance, and electroactive reaction site richness of the sodium ferric pyrophosphate positive electrode material, has high capacity, stable electrochemical performance, and excellent rate performance, and is suitable for the industrial production of sodium ion batteries.
Smart Images

Figure CN119447226A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ion battery positive electrode materials, and in particular to a high-entropy porous sodium iron phosphate pyrophosphate positive electrode material and a preparation method thereof. Background Art
[0002] As an important energy storage device, lithium-ion batteries are widely used in electronic equipment, new energy vehicles, energy storage power stations and other fields. As the core raw material of lithium-ion batteries, lithium resources have limited reserves, uneven distribution and are difficult to extract. With the growing demand for lithium-ion batteries in the energy storage market, the shortage of lithium resources has become the biggest challenge facing the large-scale application of lithium-ion batteries in the future. Therefore, finding new energy storage devices that can replace lithium-ion batteries is the key to solving the above problems.
[0003] Compared with lithium resources, sodium resources have the advantages of abundant reserves, wide distribution, and low development costs. Considering the resource advantages of sodium, the research on sodium-ion batteries has attracted much attention in the industry in recent years. Compared with lithium-ion batteries, the larger radius of sodium ions in sodium-ion batteries makes it more difficult for sodium ions to diffuse inside the electrode material, resulting in a lower energy density of the battery. Therefore, the development of electrode materials with high sodium storage capacity and good recycling performance, especially positive electrode materials, is the key to improving the energy density of sodium-ion batteries.
[0004] As an iron-based polyanion cathode material, sodium iron pyrophosphate has a high theoretical capacity (97-129 mAh / g), a high operating voltage (~3.1 V, Na + / Na) and low volume expansion (~4%), it is a positive electrode material with good application prospects and cost competitiveness. However, the sodium iron phosphate synthesized by the traditional solid-state method has poor electronic conductivity, low impurities, low voltage, poor cycle stability and poor reversibility of the material, which is difficult to meet the requirements of energy storage applications. Nanoparticles, uniform carbon coatings and the addition of conductive materials are common strategies to overcome the above problems.
[0005] For example, Chinese patent CN116675207B discloses an iron-based phosphate pyrophosphate material and its preparation method and application. A sodium source, an iron source, a phosphorus source, a carbon source and a solvent are mixed and centrifugal spray dried, and then low-temperature calcined and high-temperature calcined in sequence. The obtained iron-based phosphate pyrophosphate material is a secondary particle composed of primary particles, and has a high tap density and energy density, but the conductivity is still insufficient, resulting in poor rate performance and cycle stability, making it difficult to achieve industrial production.
[0006] In the prior art, when thick electrodes are used, the electrolyte infiltration effect is poor due to the thickness of the material, the ion transmission path becomes longer, and the shuttling of sodium ions between the positive and negative electrodes is hindered. The pole pieces that are not in contact with the electrolyte cannot participate in the battery electrochemical reaction. At the same time, the battery interface resistance increases, affecting the rate performance, discharge capacity and service life of sodium ion batteries (SIBs). Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high-entropy porous sodium iron phosphate pyrophosphate positive electrode material and a preparation method thereof. For the first time, it is proposed to use high-entropy porous construction and interfacial carbon coating synergistic treatment to prepare a high-entropy porous sodium iron phosphate pyrophosphate positive electrode material, which greatly improves the structural stability and specific surface area of the sodium iron phosphate pyrophosphate. Compared with other sodium iron phosphates, the high-entropy porous sodium iron phosphate pyrophosphate has faster electron transmission speed, shorter ion diffusion distance, richer electroactive reaction sites, higher gram capacity, stable electrochemical performance, and excellent rate performance.
[0008] The present invention provides a high entropy porous sodium iron phosphate pyrophosphate positive electrode material, wherein the positive electrode material uses sodium iron phosphate pyrophosphate-transition metal as a matrix material and is coated with a carbon layer on the surface;
[0009] The specific surface area of the high entropy porous sodium iron phosphate pyrophosphate positive electrode material is 20 to 30 m 2 / g;
[0010] The chemical formula of the sodium iron pyrophosphate-transition metal is:
[0011] Na4Fe 3-x M x (PO4)2P2O7;
[0012] The transition metal M includes at least five of Ti, Cr, Mn, Co, Ni, Cu, Zn, Y, Zr, Ag, and Mo.
[0013] As a preferred technical solution of the present invention, the carbon layer thickness of the high entropy porous sodium iron phosphate pyrophosphate positive electrode material is 3 to 10 nm.
[0014] As a preferred technical solution of the present invention, the content of each transition metal element in the sodium iron phosphate pyrophosphate-transition metal matrix is 500-5000ppm. For example, 500ppm, 1000ppm, 2000ppm, 3000ppm, 4000ppm, 5000ppm, etc., which can effectively improve the ionic and electronic conductivity of the positive electrode material, thereby improving its rate performance.
[0015] Compared with the problems of single-element / double-element oxide coating, such as unstable coating layer structure and poor ion and electronic conductivity, the sodium iron pyrophosphate-transition metal matrix material provided by the present invention has excellent structural stability and ion and electronic conductivity.
[0016] The present invention also provides a method for preparing the high entropy porous sodium iron phosphate pyrophosphate positive electrode material, comprising the following steps:
[0017] (7) mixing a sodium source, an iron source, a phosphorus source, a carbon source, and a transition metal compound in a set ratio to obtain a mixed powder;
[0018] (8) placing the mixed powder obtained in step (1) in a ball mill, adding a solvent and performing wet ball milling to obtain a fluid slurry;
[0019] (9) drying the fluid slurry obtained in step (2) to obtain a precursor powder;
[0020] (10) pre-sintering the precursor powder obtained in step (3) under an inert atmosphere;
[0021] (11) grinding the pre-sintered material obtained in step (4), and then continuing to heat up under the protection of an inert atmosphere for high-temperature sintering;
[0022] (12) The high-temperature sintered material obtained in step (5) is crushed and ground to obtain a high-entropy porous sodium iron phosphate pyrophosphate positive electrode material.
[0023] In a preferred embodiment, in step (1), the sodium source includes at least one of sodium carbonate, sodium bicarbonate, sodium dihydrogen carbonate, sodium acetate, and sodium ethoxide.
[0024] In a preferred embodiment, in step (1), the iron source includes at least one of ferric phosphate, ferrous phosphate, ferrous oxalate, ferrous oxalate, and ferrous acetate.
[0025] In a preferred embodiment, in step (1), the phosphorus source includes at least one of sodium pyrophosphate, sodium phosphite, sodium metaphosphate, sodium dihydrogen phosphate, ammonium hypophosphite, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate.
[0026] In a preferred embodiment, in step (1), the carbon source includes at least one of D-glucuronic acid, furanone, and ethyl lactate.
[0027] In a preferred embodiment, in step (1), the molar ratio of the sodium source, the iron source and the phosphorus source is 4:3:4; and the carbon source is 5-15% of the total mass of the sodium source, the iron source and the phosphorus source.
[0028] In a preferred embodiment, in step (1), the transition metal compound is selected from any one or more of the nitrates, sulfates, chlorides and acetates corresponding to the respective metals.
[0029] In a preferred embodiment, in step (2), the ball-to-material ratio in wet ball milling is (10-20):1 (mass ratio).
[0030] In a preferred embodiment, in step (2), the solvent used for wet ball milling includes at least one of water, ethanol and ethylene glycol.
[0031] In a preferred embodiment, in step (3), the fluid slurry is placed in a blast drying oven for drying at a temperature of 50 to 200° C. for a drying time of 10 to 16 hours.
[0032] In a preferred embodiment, in step (4), the precursor powder is pre-sintered at 300-450° C. under the protection of an inert atmosphere, with a heating rate of 5° C. / min and a holding time of 2-5 h.
[0033] In a preferred embodiment, in step (5), the pre-sintered material is ground and then heated to 600-900° C. for high-temperature calcination under the protection of an inert atmosphere, with a heating rate of 5° C. / min and a holding time of 8-15 h.
[0034] Specifically, the present invention provides a method for preparing a high entropy porous sodium iron phosphate pyrophosphate positive electrode material, comprising the following steps:
[0035] (1) adding a sodium source, an iron source, and a phosphorus source in a molar ratio of 4:3:4 into a mortar; then adding a carbon source at a rate of 5 to 15% of the total mass of the sodium source, the iron source, and the phosphorus source; then adding a transition metal compound, and finally grinding and mixing;
[0036] (2) After step (1) is completed, the ground material is placed in a ball mill, and then ball mill beads are added at a mass ratio of (10-20):1, and then an appropriate amount of solvent is added for wet ball milling. The ball milling speed is 400-600 rpm / min, and the ball milling time is 4-8 hours;
[0037] (3) After step (2) is completed, the ball milling is stopped, and the fluid slurry is collected and placed in a blast drying oven for drying at a temperature of 50 to 200° C. for a drying time of 10 to 16 hours; then the slurry is transferred to a mortar for grinding again to obtain a precursor powder material;
[0038] (4) Pre-sintering the precursor material at 300-450°C under inert atmosphere protection, with a heating rate of 5°C / min and a holding time of 2-5h;
[0039] (5) grinding the pre-sintered material, and then heating it to 600-900°C for high-temperature calcination at a heating rate of 5°C / min and a holding time of 8-15h;
[0040] (6) Collect the sintered materials, crush and grind them to obtain high entropy porous sodium iron phosphate pyrophosphate positive electrode material.
[0041] When preparing the positive electrode slurry, the high entropy porous sodium iron phosphate pyrophosphate positive electrode material is ground and mixed with acetylene black and binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) is used as a solvent to prepare the slurry. The slurry is fully ground and stirred to dissolve the PVDF in the NMP, and then the slurry is evenly coated on the aluminum foil with a coating thickness of 200 to 800 μm (after drying), dried in a 60°C forced air drying oven for more than 2 hours, and then placed in a vacuum drying oven at 80°C for 12 hours. The discs are cut into discs with a slicer for standby use, and the above-mentioned electrode pieces are placed in an argon-protected glove box as working electrodes, and the metal sodium sheet is assembled into a CR2016 button battery as a counter electrode; the test voltage range is 1.5 to 4.2V.
[0042] In the method for assembling a sodium ion battery described above, during the process of assembling the sodium ion battery, a glass fiber diaphragm or a polypropylene diaphragm is selected as the diaphragm, the electrolyte is a 1 mol / L sodium perchlorate solution or a sodium hexafluorophosphate solution, and the solvent system is ethylene carbonate (EC), diethylene carbonate (DEC) (volume ratio of 1:1) and 5 vol.% fluoroethylene carbonate (FEC).
[0043] The method of the present invention prepares a high entropy porous sodium iron phosphate pyrophosphate positive electrode material. The method is divided into two steps: precursor preparation and precursor calcination. First, a raw material sodium source, an iron source, a phosphorus source, a carbon source and a transition metal compound are mixed in a certain proportion by a wet grinding process, and then the mixture is wet ground as a precursor material, and then the sodium ions are controlled in a high temperature solid phase environment by controlling the inert atmosphere and the parameters such as the heating rate, the pre-burning temperature, the pre-burning time, the calcination temperature and the calcination time during the calcination process to generate high entropy porous sodium iron phosphate pyrophosphate.
[0044] The present invention also provides an evaluation method for assembling a button half-cell with a high-entropy porous sodium iron phosphate pyrophosphate positive electrode material, using sodium metal as the negative electrode, and matching an electrolyte system and a diaphragm material suitable for sodium iron phosphate pyrophosphate of a sodium ion battery.
[0045] The beneficial technical effects of the present invention are:
[0046] The present invention proposes a complete solid-phase technical route for synthesizing a sodium-ion battery high-entropy porous sodium iron phosphate pyrophosphate positive electrode material by using a sodium source, an iron source, a phosphorus source, a carbon source and a transition metal compound as raw materials. The process is simple and can be fully applicable to industrial production. And the present invention can produce products with excellent effects and meet the requirements through the improvement of the process (especially the control of ball milling time and sintering time, temperature and heating rate). The present invention clarifies the complete solid-phase synthesis technical route from raw materials to high-entropy porous sodium iron phosphate pyrophosphate, which is fully applicable to industrial production, and it is feasible to use sodium instead of lithium resources to solve the above problems.
[0047] The present invention adopts high-entropy porous construction and interfacial carbon coating synergistic treatment to prepare a high-entropy porous sodium iron phosphate pyrophosphate positive electrode material, which greatly improves the structural stability and specific surface area of the sodium iron phosphate pyrophosphate. After the electrolyte is added, the capillary effect can promote the infiltration of the electrolyte, especially when assembled into a battery, the electrocapillary effect further accelerates the infiltration of the electrolyte. The electrochemical performance is still very stable when applied to thick electrode sheets, which solves the problem in the prior art that "when thick electrodes are used, the electrolyte infiltration effect is poor due to the thick material, the ion transmission path becomes longer, and the shuttling of sodium ions between the positive and negative electrodes is hindered. The electrode sheets that are not in contact with the electrolyte cannot participate in the battery electrochemical reaction, and the battery interface resistance increases, affecting the rate performance, discharge capacity and service life of SIBs."
[0048] The various transition metal elements introduced into the high entropy porous sodium iron phosphate pyrophosphate positive electrode material of the present invention help to adapt to local changes in the material, make the crystal structure more stable, effectively improve the electronic conductivity and interface stability of the sodium iron phosphate pyrophosphate positive electrode material, and have excellent electrochemical performance. The high entropy porous sodium iron phosphate pyrophosphate positive electrode material has at least improved ion conductivity and the advantage of reducing the diffusion impedance of sodium ions in the sodium iron phosphate pyrophosphate positive electrode material; and the sodium ion battery containing the sodium iron phosphate pyrophosphate positive electrode material also has corresponding beneficial effects, which can achieve lower internal resistance and obtain better battery kinetic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 These are SEM and HRTEM images of the high-entropy porous sodium iron phosphate pyrophosphate positive electrode material for sodium ion battery obtained in Example 1.
[0050] Figure 2 This is the BET diagram of the high entropy porous sodium iron phosphate pyrophosphate positive electrode material for sodium ion battery obtained in Example 1.
[0051] Figure 3 This is the first charge and discharge curve of the high entropy porous sodium iron phosphate pyrophosphate positive electrode material for sodium ion battery obtained in Example 1 at a current of 0.1C.
[0052] Figure 4This is the first charge and discharge curve of the high entropy porous sodium iron phosphate pyrophosphate positive electrode material for sodium ion battery obtained in Example 1 at a current of 1C.
[0053] Figure 5 The sodium ion battery with high surface loading (10 mg cm) obtained in Example 1 -2 ) Long cycle diagram of high entropy porous sodium iron phosphate pyrophosphate cathode material at 0.1C current.
[0054] Figure 6 The sodium ion battery with high surface loading (10 mg cm) obtained in Example 1 -2 ) Rate performance diagram of high entropy porous sodium iron phosphate pyrophosphate positive electrode material. DETAILED DESCRIPTION
[0055] The specific implementation modes of the present invention will be described clearly and completely below with reference to the accompanying drawings.
[0056] Obviously, the described embodiments are only used to explain the present invention, and are not used to limit the present invention. Those skilled in the art may make some non-essential changes and adjustments based on the contents of the present invention, which all fall within the protection scope of the present invention.
[0057] Example 1
[0058] A method for preparing a high entropy porous sodium iron phosphate pyrophosphate positive electrode material, comprising:
[0059] 95.98g of disodium hydrogen phosphate, 86.32g of ferrous oxalate, 18.23g of furanone, and titanium chloride, zirconium nitrate, copper acetate, yttrium nitrate, chromium nitrate, and silver acetate were weighed and added to the grinding for mixing according to the contents of Ti, Zr, Cu, Y, Cr, and Ag in the sodium iron pyrophosphate-transition metal matrix of 500ppm, 1000ppm, 1500ppm, 1300ppm, 1200ppm, and 1400ppm; after mixing, the mixed materials were added to a ball mill, and then ball milling beads were added at a mass ratio of 15:1 of ball to material ratio, and then 300g of ethanol was added for wet ball milling, the ball milling speed was 500rpm / min, and the ball milling time was 5h; after the wet ball milling was completed, the fluid slurry was collected and placed in a blast drying oven for drying, the drying temperature was 60°C, and the drying time was 12h; after the drying was completed, the material was collected and then transferred to a mortar for grinding again to obtain a precursor powder material.
[0060] The precursor powder material is transferred into a tube furnace for sintering. The air in the furnace tube is evacuated with 99.999% high-purity argon gas, and then the high-purity argon atmosphere is maintained for sintering. First, the temperature is raised to 350℃ for 4 hours of pre-sintering at a heating rate of 5℃ / min; then the temperature is raised to 700℃ for 12 hours of calcination at a heating rate of 5℃ / min, and then the temperature is lowered to room temperature after calcination.
[0061] The sintered materials were collected, put into a mortar for crushing and grinding to obtain a high-entropy porous sodium iron phosphate pyrophosphate positive electrode material.
[0062] The prepared high entropy porous sodium iron phosphate pyrophosphate positive electrode material was assembled into a button half-cell for capacity testing. The specific steps were as follows: the synthesized high entropy porous sodium iron phosphate pyrophosphate powder material was ground and mixed with acetylene black and binder polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1 to prepare a mixture powder, and then N-methylpyrrolidone (NMP) and the mixture powder were added in a mass ratio of 4:1. The NMP solvent was fully ground and stirred to dissolve PVDF in NMP to obtain a positive electrode slurry; then a 250 μm coating scraper was used to The positive electrode slurry is evenly coated on aluminum foil and dried in a 60°C forced air drying oven for more than 2 h, then placed in a vacuum drying oven at 80°C and dried for 12 h, and cut into discs with a slicer for later use. The above-mentioned electrode pieces are placed in an argon-protected glove box as working electrodes, glass fiber as diaphragms, and metal sodium sheets as counter electrodes to be assembled into CR2016 button cells. The electrolyte is sodium perchlorate electrolyte (1MNaClO4, EC:DEC=1:1 (volume ratio) and 5vol.% FEC), and the test voltage range is 1.5 to 4.2V.
[0063] To test the material's thick loading (10 mg cm -2 ) when the electrochemical performance was measured, the above steps were repeated to obtain the positive electrode slurry, and the positive electrode slurry was evenly coated on the aluminum foil using a 750 μm coating scraper, and the above steps were repeated to assemble and test the battery.
[0064] Example 2
[0065] A method for preparing a high entropy porous sodium iron phosphate pyrophosphate positive electrode material, comprising:
[0066] Weigh 42.39g of sodium carbonate, 90.49g of ferric phosphate, 23.01g of ammonium dihydrogen phosphate, 15.59g of furanone, and titanium chloride, zirconium nitrate, copper acetate, yttrium nitrate, and chromium nitrate calculated according to the contents of Ti, Zr, Cu, Y, and Cr in the sodium iron pyrophosphate-transition metal matrix of 500ppm, 800ppm, 1200ppm, 700ppm, and 1000ppm, and add them to the grinding for mixing; after mixing, add the mixed materials to a ball mill, then add ball mill beads at a mass ratio of 15:1, and then add 300g of ethanol for wet ball milling, the ball milling speed is 500rpm / min, and the ball milling time is 5h; after the wet ball milling is completed, collect the fluid slurry and put it into a blast drying oven for drying, the drying temperature is 60°C, and the drying time is 12h; after the drying is completed, collect the material, and then transfer it to a mortar for grinding again to finally obtain a precursor powder material.
[0067] The sintering step was performed in the same manner as in Example 1. The sintered materials were collected, sieved, and finally subjected to air flow milling to obtain a high entropy porous sodium iron phosphate pyrophosphate positive electrode material. The battery assembly and testing steps were performed in the same manner as in Example 1.
[0068] Example 3
[0069] A method for preparing a high entropy porous sodium iron phosphate pyrophosphate positive electrode material, comprising:
[0070] Weigh 67.21g sodium bicarbonate, 90.49g ferric phosphate, 23.01g ammonium dihydrogen phosphate, 18.07g furanone, and zirconium nitrate, nickel acetate, cobalt nitrate, chromium nitrate, and silver acetate according to the content of Zr, Ni, Co, Cr, and Ag in the sodium iron pyrophosphate-transition metal matrix of 4200ppm, 4500ppm, 4600ppm, 4800ppm, and 4300ppm, and add them to the grinding for mixing; after mixing, add the mixed materials to the ball mill, then add ball milling beads at a mass ratio of 15:1 of ball to material ratio, and then add 300g ethanol for wet ball milling, the ball milling speed is 500rpm / min, and the ball milling time is 5h; after the wet ball milling is completed, collect the fluid slurry and put it into a blast drying oven for drying, the drying temperature is 60°C, and the drying time is 12h; after drying, collect the material, and then transfer it to a mortar for grinding again to obtain a precursor powder material.
[0071] The sintering step was performed in the same manner as in Example 1. The sintered materials were collected, sieved, and finally subjected to air flow milling to obtain a high entropy porous sodium iron phosphate pyrophosphate positive electrode material. The battery assembly and testing steps were performed in the same manner as in Example 1.
[0072] Example 4
[0073] A method for preparing a high entropy porous sodium iron phosphate pyrophosphate positive electrode material, comprising:
[0074] 95.98g of disodium hydrogen phosphate, 104.36g of ferrous acetate, 20.03g of D-glucuronic acid, and titanium chloride, zirconium nitrate, nickel acetate, cobalt nitrate, chromium nitrate, and silver acetate were weighed and added to the grinding for mixing according to the contents of Ti, Zr, Ni, Co, Cr, and Ag in the sodium iron pyrophosphate-transition metal matrix of 4000ppm, 4200ppm, 4500ppm, 4600ppm, 4800ppm, and 4300ppm; after mixing, the mixed materials were added to a ball mill, and then ball milling beads were added at a mass ratio of 15:1 of ball-to-material ratio, and 300g of ethanol was added for wet ball milling, the ball milling speed was 500rpm / min, and the ball milling time was 5h; after the wet ball milling was completed, the fluid slurry was collected and placed in a blast drying oven for drying, the drying temperature was 60°C, and the drying time was 12h; after the drying was completed, the materials were collected and then transferred to a mortar for grinding again to obtain a precursor powder material.
[0075] The sintering step was performed in the same manner as in Example 1. The sintered materials were collected, sieved, and finally subjected to air flow milling to obtain a high entropy porous sodium iron phosphate pyrophosphate positive electrode material. The battery assembly and testing steps were performed in the same manner as in Example 1.
[0076] Example 5
[0077] A method for preparing a high entropy porous sodium iron phosphate pyrophosphate positive electrode material, comprising:
[0078] 95.98g of disodium hydrogen phosphate, 86.32g of ferrous oxalate, 18.23g of D-glucuronic acid, and titanium chloride, zirconium nitrate, nickel acetate, cobalt nitrate, and chromium nitrate were weighed according to the contents of Ti, Zr, Ni, Co, and Cr in the sodium iron pyrophosphate-transition metal matrix of 4000ppm, 4200ppm, 4500ppm, 4600ppm, and 4800ppm, and added to the grinding for mixing; after mixing, the mixed materials were added to a ball mill, and then ball milling beads were added at a mass ratio of 15:1 of ball to material ratio, and then 300g of ethanol was added for wet ball milling, the ball milling speed was 500rpm / min, and the ball milling time was 5h; after the wet ball milling was completed, the fluid slurry was collected and placed in a blast drying oven for drying, the drying temperature was 60°C, and the drying time was 12h; after the drying was completed, the material was collected and then transferred to a mortar for grinding again to obtain a precursor powder material.
[0079] The sintering step is performed in the same manner as in Example 1. The sintered materials are collected, sieved, and finally subjected to air flow milling to obtain a high entropy porous sodium iron phosphate pyrophosphate positive electrode material.
[0080] The battery assembly and testing steps were carried out in the same manner as in Example 1.
[0081] Example 6
[0082] A method for preparing a high entropy porous sodium iron phosphate pyrophosphate positive electrode material, comprising:
[0083] 95.98g of disodium hydrogen phosphate, 86.32g of ferrous oxalate, 18.23g of ethyl lactate, and titanium chloride, zirconium nitrate, nickel acetate, cobalt nitrate, chromium nitrate, and manganese sulfate were weighed according to the contents of Ti, Zr, Ni, Co, Cr, and Mn in the sodium iron pyrophosphate-transition metal matrix of 4000ppm, 4200ppm, 4500ppm, 4600ppm, 4800ppm, and 4300ppm, and added to the grinding for mixing; after mixing, the mixed materials were added to a ball mill, and then ball milling beads were added at a mass ratio of 15:1 of ball to material ratio, and then 300g of ethanol was added for wet ball milling, the ball milling speed was 500rpm / min, and the ball milling time was 5h; after the wet ball milling was completed, the fluid slurry was collected and placed in a blast drying oven for drying, the drying temperature was 60°C, and the drying time was 12h; after the drying was completed, the material was collected and then transferred to a mortar for grinding again to obtain a precursor powder material.
[0084] The sintering step is performed in the same manner as in Example 1. The sintered materials are collected, sieved, and finally subjected to air flow milling to obtain a high entropy porous sodium iron phosphate pyrophosphate positive electrode material.
[0085] The battery assembly and testing steps were carried out in the same manner as in Example 1.
[0086] Example 7
[0087] A method for preparing a high entropy porous sodium iron phosphate pyrophosphate positive electrode material, comprising:
[0088] Weigh 67.21g sodium bicarbonate, 90.49g ferric phosphate, 23.01g ammonium dihydrogen phosphate, 18.07g ethyl lactate, and nickel acetate, manganese sulfate, cobalt nitrate, chromium nitrate, and molybdenum nitrate calculated according to the content of Ni, Mn, Co, Cr, and Mo in the sodium iron pyrophosphate-transition metal matrix of 4200ppm, 4500ppm, 4600ppm, 4800ppm, and 4300ppm, and add them to the grinding for mixing; after mixing, add the mixed materials to a ball mill, then add ball milling beads at a mass ratio of 15:1 of ball to material ratio, and then add 300g ethanol for wet ball milling, the ball milling speed is 500rpm / min, and the ball milling time is 5h; after the wet ball milling is completed, collect the fluid slurry and put it into a blast drying oven for drying, the drying temperature is 60°C, and the drying time is 12h; after the drying is completed, collect the material, and then transfer it to a mortar for grinding again to obtain a precursor powder material.
[0089] The sintering step was performed in the same manner as in Example 1. The sintered materials were collected, sieved, and finally subjected to air flow milling to obtain a high entropy porous sodium iron phosphate pyrophosphate positive electrode material. The battery assembly and testing steps were performed in the same manner as in Example 1.
[0090] Table 1 The electrochemical performance test of the high entropy porous sodium iron phosphate pyrophosphate positive electrode material in each embodiment under the voltage window of 1.5-4.2V is respectively the first cycle charge and discharge capacity at 0.1C and 1C and the capacity change of 200 cycles under 1C current. The results are shown in Table 1 below:
[0091] Table 1
[0092]
[0093] The invention discloses a high-entropy porous sodium iron phosphate pyrophosphate positive electrode material and a preparation method thereof. The method realizes a low-cost industrialized solid-phase synthesis technology of a high-entropy porous sodium iron phosphate pyrophosphate positive electrode material. The method has a reasonable design, a simple process, and is convenient for large-scale production. The synthesized high-entropy porous sodium iron phosphate pyrophosphate positive electrode material has a faster electron transmission speed, a shorter ion diffusion distance, more abundant electroactive reaction sites, a high gram capacity, and stable electrochemical performance. The high-entropy porous sodium iron phosphate pyrophosphate positive electrode material can be used as a preferred positive electrode material for future commercial sodium ion batteries.
[0094] In order to ensure that the above are only preferred embodiments of the present invention, only the implementation methods of the present invention are described, and the patent scope of the present invention is not limited thereby. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly used in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A high entropy porous sodium iron phosphate pyrophosphate positive electrode material, characterized in that: The positive electrode material uses sodium iron phosphate pyrophosphate-transition metal as the base material, and the surface is coated with a carbon layer; The specific surface area of the high entropy porous sodium iron phosphate pyrophosphate positive electrode material is 20 to 30 m 2 / g; The chemical formula of the sodium iron pyrophosphate-transition metal is: Na4Fe 3-x M x (PO4)2P2O7; The transition metal M includes at least five of Ti, Cr, Mn, Co, Ni, Cu, Zn, Y, Zr, Ag, and Mo.
2. According to claim 1, a high entropy porous sodium iron phosphate pyrophosphate positive electrode material, characterized in that: The carbon layer thickness of the high entropy porous sodium iron phosphate pyrophosphate positive electrode material is 3 to 10 nm.
3. The high entropy porous sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: The content of each transition metal element in the sodium iron pyrophosphate-transition metal matrix is 500-5000 ppm.
4. The method for preparing the high entropy porous sodium iron phosphate pyrophosphate positive electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) mixing a sodium source, an iron source, a phosphorus source, a carbon source and a transition metal compound in a set ratio to obtain a mixed powder; (2) placing the mixed powder obtained in step (1) in a ball mill, adding a solvent and performing wet ball milling to obtain a fluid slurry; (3) drying the fluid slurry obtained in step (2) to obtain a precursor powder; (4) pre-sintering the precursor powder obtained in step (3) under the protection of an inert atmosphere; (5) grinding the pre-sintered material obtained in step (4), and then continuing to heat up under the protection of an inert atmosphere for high-temperature sintering; (6) The high-temperature sintered material obtained in step (5) is crushed and ground to obtain a high-entropy porous sodium iron phosphate pyrophosphate positive electrode material.
5. The method for preparing the high entropy porous sodium iron phosphate pyrophosphate positive electrode material according to claim 4, characterized in that: In step (1), the sodium source includes at least one of sodium carbonate, sodium bicarbonate, sodium dihydrogen carbonate, sodium acetate, and sodium ethoxide; In step (1), the iron source includes at least one of ferric phosphate, ferrous phosphate, ferrous oxalate, ferrous oxalate, and ferrous acetate; In step (1), the phosphorus source includes at least one of sodium pyrophosphate, sodium phosphite, sodium metaphosphate, sodium dihydrogen phosphate, ammonium hypophosphite, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate; In step (1), the carbon source includes at least one of D-glucuronic acid, furanone, and ethyl lactate; In step (1), the molar ratio of the sodium source, the iron source and the phosphorus source is 4:3:4; the carbon source is 5-15% of the total mass of the sodium source, the iron source and the phosphorus source; In step (1), the transition metal compound is selected from any one or more of the nitrates, sulfates, chlorides and acetates corresponding to each metal.
6. The method for preparing the high entropy porous sodium iron phosphate pyrophosphate positive electrode material according to claim 4, characterized in that: In step (2), the ball-to-material ratio of wet ball milling is (10-20):
1.
7. The method for preparing the high entropy porous sodium iron phosphate pyrophosphate positive electrode material according to claim 4 or 6, characterized in that: In step (2), the solvent used in wet ball milling includes at least one of water, ethanol and ethylene glycol.
8. The method for preparing the high entropy porous sodium iron phosphate pyrophosphate positive electrode material according to claim 4, characterized in that: In step (3), the fluid slurry is placed in a blast drying oven for drying at a drying temperature of 50 to 200° C. for a drying time of 10 to 16 hours.
9. The method for preparing the high entropy porous sodium iron phosphate pyrophosphate positive electrode material according to claim 4, characterized in that: In step (4), the precursor powder is pre-sintered at 300-450° C. under inert atmosphere protection, with a heating rate of 5° C. / min and a holding time of 2-5 h.
10. The method for preparing the high entropy porous sodium iron phosphate pyrophosphate positive electrode material according to claim 4, characterized in that: In step (5), the pre-sintered material is ground and then heated to 600-900° C. for high-temperature calcination under the protection of an inert atmosphere, with a heating rate of 5° C. / min and a holding time of 8-15 h.
Citation Information
Patent Citations
High-entropy ferric sodium pyrophosphate sodium ion battery positive electrode material and preparation method thereof
CN116404154A
Doped modified ferric sodium pyrophosphate positive electrode material and preparation method thereof
CN116682946A
Positive pole piece and preparation method thereof, energy storage device and power utilization device
CN116741988A
Porous ferric sodium pyrophosphate / carbon composite material as well as preparation method and application thereof
CN116799131A
High-entropy ferric sodium phosphate pyrophosphate precursor and high-entropy ferric sodium phosphate pyrophosphate positive electrode material
CN118684208A
Cited By
Porous ferric sodium pyrophosphate positive electrode precursor and preparation method and application thereof
CN120573667A